Evaluation of antioxidant and antimutagenic activities of aluminum chloride - İnci Rana Karaca; Aysel Uğur; Nurdan Saraç (Istanbul University, 2019)
Purpose Hemostatic agents are used to control hemorrhage and the gingival crevicular fluid for dental applications. In this study; the antimutagenic and antioxidant activities of aluminum chloride (AlCl3), a topical hemostatic agent used especially in the fields of dermatology and dentistry, were determined. To our knowledge, this is the first study that investigates these properties. Materials and Methods The antioxidant activity was determined by DPPH free radical scavenging and β-carotene-linoleic acid bleaching assays. The antimutagenic activity was evaluated with the Ames Salmonella/ microsome mutagenicity test using Salmonella typhimurium TA98 and TA100 strains. Results The total antioxidant activity of AlCl3, determined by β-carotene bleaching assay was found to be 25.59 ± 2.55% and the DPPH scavenging activity of AlCl3 was determined as 17.49 ± 3.07%. AlCl3 showed not any mutagenicity at the tested concentrations by the AMES test used S. typhimurium TA98 and TA100. This drug demonstrated antimutagenic effects at the test concentrations and the strongest antimutagenic activity was observed on 1.25 mg·mL-1/plate concentration of AlCl3. Conclusion AlCl3 showed potent antimutagenic and antioxidant activities and these properties are significant for dentistry and dermatology.